CLINICOPATHOLOGIC CRITERIA OF PERINATAL BRAIN INJURY IN CHILDREN BORN WITH LOW AND EXTREMELY LOW BODY WEIGHT - M. P. Yakovenko; E. I. Kleshenko (Кубанский научный медицинский вестник, 2017)
Aim. The objective of this study was to establish structural changes in the brain of preterm neonates born with low and extremely low body weight, with perinatal brain damage of moderate severity by neurotractography. Materials and methods. 48 children born with very low and extremely low body weight were examined. Structural changes according to neurosonography were revealed in all. Neurotractography was performed before discharge from the nursing department.Results. A significant difference in the neurological status before discharge was not detected in children. The area of interest was the crus posterius capsulae internae during neurotractography. Reduction of FA and increase of ADC was detected in three cases. These children had a motormental retardation at the adjusted age of 12 months.Conclusions. Neuropathography results can increase the accuracy of later neurologic prognosis. If significant changes in the neurotractography are not recorded, then a favorable neurological prognosis is predicted